Voices in the mirror an autobiography - Parks, Gordon 1912-2006 (Doubleday, 1990)
Presents the autobiography of Gordon Parks, a photographer, writer, and director who worked his way from homelessness to success. Explores Parks's ability to break down barriers to become the first black photographer at "Vogue" and "Life," and the first black screenwriter and director in Hollywood. Describes his relationships with Ingrid Bergman, Roberto Rossellini, Malcom X, Elijah Muhammad, and Muhammad Ali. Also examines his different life experiences in Minnesota; Washington, D.C.; Paris; Rio; and Harlem.
Keywords: Parks, Gordon <1912-2006>; Parks, Gordon -- 1912-2006; African American photographers -- Biography; Photographers -- United States -- Biography; Autobiografie; USA; Aufsatzsammlung; Biografie